2004
DOI: 10.1557/proc-824-cc8.35
|View full text |Cite
|
Sign up to set email alerts
|

Geopolymers for the Immobilization of Radioactive Waste

Abstract: Geopolymers are made by adding aluminosilicates to concentrated alkali solutions for dissolution and subsequent polymerization to form a solid. They are amorphous to semicrystalline three dimensional aluminosilicate networks. Although they have been used in several applications their widespread use is restricted due to lack of long term durability studies and detailed scientific understanding. Three important tools for the study of geopolymers are transmission electron microscopy (TEM), solid state magic angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 2 publications
(2 reference statements)
0
16
0
2
Order By: Relevance
“…These processes are responsible for fluctuations of the compressive strength and final strength improvement of the samples when immersed in the magnesium sulfate solution. Ca +2 and Mg +2 ions can be accommodated in aluminasilicate gel as network-modifying cations [39].…”
Section: Effect Of Magnesium Content In Dolomitementioning
confidence: 99%
“…These processes are responsible for fluctuations of the compressive strength and final strength improvement of the samples when immersed in the magnesium sulfate solution. Ca +2 and Mg +2 ions can be accommodated in aluminasilicate gel as network-modifying cations [39].…”
Section: Effect Of Magnesium Content In Dolomitementioning
confidence: 99%
“…Cs is very soluble in water and the most difficult radionuclides to immobilize [6]. On the basis of the leaching rate, we can predict percentage of leaching during next the 300 years (10 half-lives of 137 Cs) and at the end of this period radioactivity will have decreased more [7].…”
Section: Radionuclides Leachabilitymentioning
confidence: 99%
“…Davidovits (1994aDavidovits ( , 1994bDavidovits ( , 1994c) is attributed with the early development and formulation of geopolymers, for which he has been awarded several patents. Khalil and Merz (1994) and Perera et al (2004) have also studied the formulation and application of geopolymers for waste solidification.…”
Section: Geopolymersmentioning
confidence: 99%
“…The material is largely amorphous with some minor crystalline structure, again dependent on the source materials. Contaminant distribution studies showed that Cs was concentrated in the amorphous phase, while Sr was present in both the amorphous and crystalline phases (Perera et al 2004).…”
Section: Geopolymersmentioning
confidence: 99%